(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The present study aimed at evaluating the adulteration in milk samples of different regions of Ludhiana, the Industrial hub of Punjab and the Manchester of India. The presence of chemical adulterants was analysed by standard methods to test the milk samples collected from six areas of Ludhiana city: Civil Lines, adjoining areas of Bus Stand, Chandigarh Road, Haibowal, Ferozepur Road and Hambran Road. All the areas of study tested negative for starch, ammonium compounds, formalin, detergent and urea whereas 86.66% adulteration was found for water followed by salt (23.33%) and acidity (6.66%). The present work provided an insight into the quality of milk consumed in the areas of study and such monitoring is pivotal for generating awareness at the level of consumer.